PENGARUH NILAI YANG DIANUT TERHADAP PREFERENSI DAN PERILAKU PEMBELIAN BUAH-BUAHAN - Syifa, Za'iemah Asy; Hartoyo, Hartoyo (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2011)
This research was based on theoretical and empirical reviews to explain the effect of values on the preferences and purchasing behavior of fruits. This research was performed by providing questionnaires to 162 college students by convenience sampling method. Pearson correlation test result showed there were significant relationships between value orientation with awareness and responsibility. Furthermore, awareness of behavior also showed strong direct relationships with responsibility, and personal norm also showed a significant relationship with habitual behavior in consuming fruits. Preference of the apple was influenced by ethnicity, value orientations, and awareness, while preference of orange was influenced by responsibility. Purchase of apple was influenced by gender and preferences, while purchasing of orange was influenced by personal norm and preference of orange. There was a tendency that with increasing values, behavior awareness, responsibility, and personal norms can increase purchasing of local fruits.